2021
DOI: 10.4236/jbm.2021.912002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <i>Momordica charantia</i> on Ovarian Ischemia-Reperfusion

Abstract: Ovarian torsion is one of the gynecological emergencies that affect ovarian tissue integrity and fertility. In this study, we aim to investigate the effects of Momordica charantia (MC) on ovarian tissue injury induced by ovarian ischemia-reperfusion. Twenty-four rats were assigned to three groups: control group, ischemia-reperfusion (I/R) group and IR + MC group. 600 mg/kg MC extract were given rats via orogastric route. 3-hour ischemia and 3-hour reperfusion were performed for IR protocol. At the end of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Asir et al studied effects of Momordica charantia on ovarian IR. They found that IR cause degenerated follicles, vascular dilatation, inflammation and fibrin accumulation in ovarian tissues 16 . In an ovarian IR study performed by Peker et al, the author investigated effects of carvacrol on ovarian tissue by immunohistochemical method.…”
Section: Discussionmentioning
confidence: 99%
“…Asir et al studied effects of Momordica charantia on ovarian IR. They found that IR cause degenerated follicles, vascular dilatation, inflammation and fibrin accumulation in ovarian tissues 16 . In an ovarian IR study performed by Peker et al, the author investigated effects of carvacrol on ovarian tissue by immunohistochemical method.…”
Section: Discussionmentioning
confidence: 99%
“…Acute abdominal pain, nausea, vomiting and fever resulting from disruption of vascular flow are among the typical clinical findings of adenxial torsion 2 . Medicinal plants are used quite frequently to prevent complications arising from ischemic damage [11][12][13] . The effect of terebinth (Pistacia terebinthus L.) oil on adnexal torsion is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It mainly affects the women of reproductive age. Early diagnosis and treatment are critical in preventing infertility (3).…”
Section: Introductionmentioning
confidence: 99%